In Situ Neutron Diffraction Study of the Deuteration of Isotopic Mg11B2 - Pitt, Mark; Webb, C.; Paskevicius, Mark; Sheptyakov, D.; Buckley, Craig; Gray, E. (American Chemical Society, 2011)
Isotopic Mg11B2 has been deuterated at 400 °C and 800 bar, with the production of β-Mg(11BD4)2 observed by in situ neutron diffraction. A natural MgB2 sample has been deuterated under similar conditions and studied ex situ by high resolution X-ray synchrotron diffraction. In both cases, quantitative phase analysis (QPA) indicates a ca. 43% yield of the high temperature (β) phase, with the rest of the sample composed of unreacted MgB2 and Mg or MgD2. A joint refinement of the neutron and X-ray synchrotron data has been performed, yielding a final β-Mg(11BD4)2 structure in space group Fddd, with new D positions. Anisotropically broadened (odd, odd, odd) reflections are attributed to microstructural features, rather than antiphase boundaries. QPA of the isotopic sample indicates ca. 10% of B atoms are in a noncrystalline state. A broad feature is evident in the ex situ X-ray synchrotron data, covering a wide d-spacing range from ca. 3.80–5.45 Å, consistent with the formation of amorphous Mg(BD4)2 and amorphous B. For both samples, macroscopic fusing occurs, forming an extremely hard phase with a glassy black appearance, which is hydrogen impermeable and inhibits further formation of β-Mg(BH4)2. The fused surface regions of the sample have been studied by transmission (TEM) and scanning (SEM) electron microscopy. TEM studies show amorphous regions on the surface, consistent with amorphous B, and a Mg–B–O–H phase.